PRINCE SAMUDRA'S TOMB AS A GROWTH GENERATOR FOR GUNUNG KEMUKUS SETTLEMENT IN SRAGEN REGENCY - Tri Hartanto; A Bamban Yuuwono; Danarti Karsono; Wahyu Prabowo (Jurnal Teknik Sipil dan Arsitektur, 2023)
The Javanese have many traditions, which illustrate that the Javanese or Javanese people in achieving their expectations are not enough just to work and pray, but there are other ways such as ritual efforts that are carried out based on their belief in various myths and the history of places considered sacredness that develops in society. One of the ritual places and has a strong mythical belief is the tomb of Prince Samudra on Gunung Kemukus, Pendem Village, Sumberlawang District, Sragen Regency, Central Java. This hill (mountain of cubes), there is the tomb of Prince Samudra, Nyai Ontrowulan and his servants. The Javanese people, especially the people around them, have a belief that the tombs are considered sacred. Then the community began to build houses and live around the tomb. The habit of people seeking blessings through the tradition of ngalap blessing, which is an activity to seek goodness from an essence, object or something that is considered by humans to have benefits and goodness, or seeking barakah (ngalap blessing) or other words "tabarruk". This tomb is also a destination for the ngalap blessing ritual by the surrounding community and from the people on the island of Java. More and more community visits have led to the growth of settlements around the tomb, where previously there were no settlements, only hills. Based on the results of research, the existence of Prince Samudra's tomb is a generator for the emergence of settlements.